Mitigation of quorum sensing mediated virulence factors of Pseudomonas aeruginosa: the role of Meldrum’s acid activated furan - Sadik, Ajmal; Viswaswar, Jithin P.; Rajamoney, Ambili; Rekha, Anjali; Raj, Darsana M.; Prakashan, Deepthi; Vasudevan, Mydhili; Visakh, J. S.; Renuka, Dhannya; Hely, Sreetha; Shaji, Sanu Korumadathil; Chandran, Prakash R.; et al. (Frontiers in Microbiology, 2024)
The rapid emergence of drug resistant pathogens is a major threat which has warranted the development of alternative strategies to combat infectious diseases. In this work, we have tested the anti-virulent activity of Meldrum's acid Activated Furan (MAF) and 1,3-dimethyl Barbituric acid Activated Furan (BAF) against C. violaceum and P. aeruginosa . It was found that MAF significantly reduced the violacein production and biofilm formation of C. violaceum at sub-inhibitory concentrations. The Quorum Sensing (QS) regulated virulence factors of P. aeruginosa including biofilm formation, motility, pigment production and elastase activity were also found to be reduced considerably at sub inhibitory concentrations of MAF.Additionally, MAF down regulated the expression of genes in the QS circuitry of P. aeruginosa, demonstrating the potential of MAF in lowering the pathogenicity of P.aeruginosa. In silico studies demonstrated the potential of MAF to compete with the signalling molecules of C. violaceum and P. aeruginosa for the QS receptor interaction. In vivo studies using C elegans demonstrated the anti-pathogenicity of MAF by enhancing the survival of P. aeruginosa infected C. elegans. . These results suggest that activated furan compounds could be potential inhibitors of QS mediated virulence factors in C. violaceum and P. aeruginosa encouraging their use in combating multidrug resistant pathogens.